Management of SARS-CoV-2 Infection: Key Focus in Macrolides Efficacy for COVID-19 - Batiha, Gaber El-Saber; Zayed, Marwa A.; Awad, Aya A.; Shaheen, Hazem M.; Mustapha, Suleiman; Herrera-Calderon, Oscar; Pagnossa, Jorge Pamplona; Algammal, Abdelazeem M.; Zahoor, Muhammad; Adhikari, Achyut; Pandey, Ishan; Elazab, Sara T.; et al. (Frontiers in Medicine, 2021)
Macrolides (e.g., erythromycin, fidaxomicin, clarithromycin and, azithromycin) are a class of bacteriostatic antibiotics commonly employed in medicine against various gram-positive and atypical bacterial species mostly related to respiratory tract infections, besides to possess anti-inflammatory and immunomodulatory effects. Coronavirus Disease 2019 (COVID‐19) is an infectious disease caused by the severe acute respiratory syndrome of coronavirus 2 (SARS-CoV-2). It was first detected in Wuhan, Hubei, China in December 2019 and resulted in a continuing pandemic. Macrolides have been extensively researched as broad adjunctive therapy for COVID-19 due to its immunostimulant abilities. Among such class of drugs, azithromycin is described as azalide, and is well known for its ability to decrease the production of pro-inflammatory cytokines, including matrix metalloproteinases, tumor necrosis factor-alpha, interleukin (IL)-6 and IL-8. In fact, a report recently published highlighted the effectiveness of combining azithromycin and hydroxychloroquine for COVID-19 treatment. Indeed, it has been underlined that azithromycin quickly prevents SARS-CoV-2 infection by raising the levels of both interferons and interferon-stimulated proteins at same time that reduces the virus replication and release. In this sense, the current review aims to evaluate the applications of macrolides for the treatment of COVID-19.